Pengaruh Kepemilikan Institusional dan Profitabilitas Terhadap Nilai Perusahaan Dengan Manajemen Laba Sebagai Variabel Intervening - Wira Ramashar; Amir Hasan (Akuntansi & Ekonomika, 2018)
This study aimed to analyze and explain: the influence of institutional ownership on firm value, the influence of institutional ownership on firm value through earnings management, the effect of profitability on firm value, the effect of profitability on firm value through management earnings, and the effect of earnings management on firm value. The study population was banking companies listed in the Indonesia Stock Exchange (BEI) in the period 2010 to 2014 with a total sample of 26 companies. Results of data analysis proves that : institutional ownership has no effect on firm value, institutional ownership positively affects the firm value to be mediated by earnings management, profitability negatively affect the firm value, profitability negatively affect the firm value to be mediated by earnings management and earnings management negatively affect the firm value. Key words : firm value, institutional ownership, profitability, and earnings management